Caracterização das condições de saúde e presença de polifarmácia em idosos institucionalizados - Gatto, Cristine Melania (2017)
To characterize the health conditions of the institutionalized elderly, to relate the occurrence of chronic diseases with the use of medication, to verify the occurrence of controversy and to identify the use of benzodiazepines among elderly people living in long-stay institutions for the elderly in the city of Passo Fundo. Method: cross -sectional, population-based study involving 222 people aged 60 years and over. A sample with a predominance of the female gender, with white skin color, above 80 years, low schooling and widows. There was a decline in knowledge, presence of chronic diseases, practice of polypharmacy (such as using 5 or more drugs) and use of benzodiazepines. In order to verify sociodemographic variables, health conditions and access to medicines and medicines, a Pearson's Chi-square test and a Fisher's exact test were used, and a linear trend was used in the crude analysis and binary logistic regression model in the adjusted analysis, with measures of effect Expressed in odds ratio. The level of significance was 5%. Results: There was a cognitive decline of 63.5% among interviewees. Of the chronic diseases, 53.8% SAH, 47.6% dementia, 34.8% chronic pain, 33.0% insomnia and 32.7% depression, are directly related to polypharmacy. The prevalence of polypharmacy was 74.5%. No statistically significant associations were identified between cognitive decline and benzodiazepine use, cognitive decline was found in those who did not use benzodiazepines. Conclusion: In this case, many problems were encountered and several sets for health services due to the need for qualified professionals and the lack of support programs for long-term care institutions for the elderly (ILPI). This study contributes to the construction of public policies that act on the health conditions of the elderly, promoting well -being, independence and vitality. However, it is necessary to deepen research involving the elderly in the condition of institutionalization and emphasizing polypharmacy.